Stranger things. v. 01, The other side - Houser, Jody (Stranger things, 2019)
"When Will Byers finds himself in the Upside Down, an impossible dark parody of his own world, he's understandably frightened. But that's nothing compared with the fear that takes hold when he realizes what's in that world with him!"--